FORECASTING THE NUMBER OF HOUSING UNITS DELIVERED IN POLAND IN THE YEARS 2010-2017 IN THE CONTEXT OF SOCIAL SECURITY - Kozicki Bartosz; Koszarek Artur (2021)
The article addresses the problem of forecasting the number of housing units delivered in Poland in 2010-2017 on the basis of primary data obtained from the Central Statistical Office in the context of social security. First, an analysis and evaluation of the time series in question was made. Subsequently, the analysed time series was divided into two segments. On the basis of the evaluation, forecasting was performed with various methods for the first part of the time series of the number of housing units completed in Poland, which consisted of 84 elements, and then the best forecasting method was selected. On the basis of that method, forecasting of the primary time series (consisting of 96 elements) of the number of housing units completed in Poland in 2010-2017 was performed retrospectively for 2018.